MODEL KOMUNIKASI ORANG TUA KEPADA ANAK DALAM QOSHOSHUL QUR’AN - Irfan Afandi (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This article attempts to find models of parent and child communication in the qoshoshul qur'an. This research is important because there are not many articles that use a circular mindset in understanding the qoshoshul of the Qur'an. In the end, understanding is stuck in the linearity of narratives of characters, events and contexts of stories without being able to see concept maps that are useful for today. The communication model between parents and children is very necessary in this day and age in the midst of the pace of the digital era. Many children communicate very little with their parents with communication technology. This study took primary data on Qur'anic verses and books of tafsir as explanations. The data is analyzed through Qur'anic qoshoshil techniques that concentrate on the characters, events and context of the verse. The results showed that many models that can be used as alternative communication models include wills, sharing experiences, advice and invitations. From the mother's side, a mother can take a non-verbal communication model such as trust in the child and trust in the child's abilities. Because, children have certain special privileges given by Allah SWT. Meanwhile, from the child's side, a child can also initiate communication but must pay attention to the ma'ruf rules. If there is a dispute in the communication process, a child should still pray for the safety and health of his parents. It is not allowed to harbor hatred for his parents.